2015
DOI: 10.1038/nprot.2015.051
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive, rapid prototyping of microfluidic devices using overhead transparencies and a laser print, cut and laminate fabrication method

Abstract: We describe a technique for fabricating microfluidic devices with complex multilayer architectures using a laser printer, a CO2 laser cutter, an office laminator and common overhead transparencies as a printable substrate via a laser print, cut and laminate (PCL) methodology. The printer toner serves three functions: (i) it defines the microfluidic architecture, which is printed on the overhead transparencies; (ii) it acts as the adhesive agent for the bonding of multiple transparency layers; and (iii) it prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 39 publications
0
116
0
3
Order By: Relevance
“…Microfluidics with its advantages of low volume consumption, flexibility, disposability, and low costs, is a powerful tool for addressing POC sample preparation challenges (Elvira et al 2013; Sackmann et al 2014; Tan et al 2015; Thompson et al 2015). Because the channel and reactor sizes are at the micrometer scale, multiple assays can be performed in a small area in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics with its advantages of low volume consumption, flexibility, disposability, and low costs, is a powerful tool for addressing POC sample preparation challenges (Elvira et al 2013; Sackmann et al 2014; Tan et al 2015; Thompson et al 2015). Because the channel and reactor sizes are at the micrometer scale, multiple assays can be performed in a small area in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Among the alternative fabrication methodologies, tonerbased techniques offer simplicity and low instrumental requirements, thus making possible their implementation in any laboratory or research center. 13,14 Toner was firstly explored for microfabrication in 2001, when Tan et al 15 suggested the use of a photocopying machine to create a high-relief master for prototyping of microfluidic devices in poly(dimetilsyloxane) (PDMS) substrate. In 2003, do Lago et al 16 proposed the direct fabrication of microfluidic devices using a laser printer for the deposition of toner layers on polyester films followed by a thermal lamination for sealing of channels at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…10 In the current study we have used cyclic polyolefins (COPs) which belong to a class of polymers employed due to their compatibility with biological materials, low autofluorescence, long shelf life and suitability for surface modification amongst others. 11,12 Multilayer alignment fabrication methodologies are commonly used to develop functional microdevices 13,14 , as lamination of polymer layers offers greater versatility and low cost. Zeonor® was chosen for this study, in conjunction with PSA (pressure sensitive adhesive), as both are suitable materials for simple fabrication and lamination methodologies.…”
Section: Introductionmentioning
confidence: 99%